2001
DOI: 10.1021/bi010736o
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Human S-Adenosylmethionine Decarboxylase Self-Processing Ester Intermediate and Mechanism of Putrescine Stimulation of Processing As Revealed by the H243A Mutant,

Abstract: S-Adenosylmethionine decarboxylase (AdoMetDC) is synthesized as a proenzyme that cleaves itself in a putrescine-stimulated reaction via an N-->O acyl shift and beta-elimination to produce an active enzyme with a catalytically essential pyruvoyl residue at the new N-terminus. N-->O acyl shifts initiate the self-processing of other proteins such as inteins and amidohydrolases, but their mechanisms in such proteins are not well understood. We have solved the crystal structure of the H243A mutant of AdoMetDC to 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
92
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(104 citation statements)
references
References 31 publications
11
92
1
Order By: Relevance
“…Mass spectrometry of proteins modified by the latter pathway revealed adducts with mass increases of ϩ57 and ϩ75 daltons resulting from the addition of CH 2 -CH 2 -CHO and the hydrate thereof (15). In contrast the mass spectrum of the M. jannaschii decarboxylase as isolated from E. coli showed that this protein is not detectably modified in vivo when expressed either at low levels (24) or at the ϳ40-fold greater levels of expression obtained in the present work (Fig.…”
Section: O Kinetic Isotope Effects and Presteady State Kinetic Stcontrasting
confidence: 49%
See 1 more Smart Citation
“…Mass spectrometry of proteins modified by the latter pathway revealed adducts with mass increases of ϩ57 and ϩ75 daltons resulting from the addition of CH 2 -CH 2 -CHO and the hydrate thereof (15). In contrast the mass spectrum of the M. jannaschii decarboxylase as isolated from E. coli showed that this protein is not detectably modified in vivo when expressed either at low levels (24) or at the ϳ40-fold greater levels of expression obtained in the present work (Fig.…”
Section: O Kinetic Isotope Effects and Presteady State Kinetic Stcontrasting
confidence: 49%
“…Bennett et al (13)). The human and potato enzymes have been characterized by crystallographic and functional studies, which have revealed much about the protein structure and active site, as well as the allosteric nature of putrescine activation (13)(14)(15)(16)(17)(18). A second class of AdoMet decarboxylase with a distinct sequence is typified by the Mg 2ϩ -dependent Escherichia coli enzyme that is composed of 12.4-and 18-kDa subunits in an (␣␤) 4 arrangement (7, 15, 19 -23).…”
mentioning
confidence: 99%
“…2A). However, the prozyme is missing several critical residues required for processing and catalytic activity (10,14,15,17,20). Therefore the prozyme is unlikely to display AdoMetDC activity and must have a unique function.…”
Section: Resultsmentioning
confidence: 99%
“…Human AdoMetDC is a homodimer, and both the processing reaction and decarboxylation of AdoMet are stimulated by putrescine (10,16). The x-ray structure shows that the active sites sit in a large cleft between ␤-sheets distal from the dimer interface and that the putrescine-binding sites are formed by a group of acidic residues in the ␤-sandwich core Ϸ15 Å from the active sites (14,17). This site is eliminated in the structure of the monomeric plant enzyme, which is fully active without putrescine (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation